A nonparametric test for seasonal unit roots - Robert M. Kunst (Institute for Advanced Studies (IHS), 2009)
We consider a nonparametric test for the null of seasonal unit roots in quarterly time series that builds on the RUR (records unit root) test by Aparicio, Escribano, and Sipols. We find that the test concept is more promising than a formalization of visual aids such as plots by quarter. In order to cope with the sensitivity of the original RUR test to autocorrelation under its null of a unit root, we suggest an augmentation step by autoregression. We present some evidence on the size and power of our procedure and we illustrate it by applications to a commodity price and to an unemployment rate.
Keywords: C12; C14; C22; 330; seasonality; nonparametric test; unit roots; Saisonbereinigung; Nichtparametrisches Verfahren; Unit Root Test; Theorie